Uji Kemampuan Produksi Fruktooligosakarida (FOS) dari Kelompok Aspergillus niger DUCC - Whinarsih, Whinarsih; Lunggani, Arina Tri; Rukmi, MG Isworo (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2013)
Prebiotic is a food supplement that can not be digested in the human’s gut, it can stimulate the growth of beneficial microorganisms in the intestine and improve human’s health. FOS is a fructan type of oligosaccharide which is have a potential as a natural prebiotic, it can be produced by several microorganisms, including A. niger group. The aim of this research was to examined the FOS production of three isolates of A. niger group from DUCC collection (i.e. DUCC F123, DUCC F129 and DUCC F102). FOS production was determined by measuring the reducing sugar using DNS method. The result showed that all isolates have the capability in producing FOS suspected kestose with the degree of polymerization 3.545; 3.215; 3.049 respectively. Keywords:FOS, fructosyltransferase, Aspergillus niger, prebiotic